Epidermal growth factor receptor and mammalian target of rapamycin as therapeutic targets in malignant glioma: current clinical status and perspectives - Ronellenfitsch, Michael Wilfried; Steinbach, Joachim Peter; Wick, Wolfgang (Targeted oncology, 2010)
Despite advances in the understanding of the molecular biology of glioblastomas (GB), these neoplasms still are incurable with conventional therapies. Current efforts therefore focus on the development of new molecular approaches that exploit the genetic aberrations of cancer cells. Based on their frequent activation or mutation in human GB and their paramount role for the maintenance of the neoplastic phenotype, both the epidermal growth factor receptor (EGFR) and the mammalian target of rapamycin (mTOR) are plausible targets for molecular therapies. However, clinical trials with drugs targeting EGFR or mTOR, so far, have produced largely disappointing results. In this article, we review strategies targeting EGFR and mTOR as therapies for malignant glioma. Recent advances in the understanding of the complex signaling network involved are highlighted and the results of clinical trials are summarized. Mechanisms of resistance are explored, and potential future directions as well as trends in preclinical and clinical development are discussed.